2014
DOI: 10.1002/2013jg002358
|View full text |Cite
|
Sign up to set email alerts
|

Sediment and carbon fluxes along a longitudinal gradient in the lower Tana River (Kenya)

Abstract: We estimated annual fluxes of suspended matter and different carbon (C) pools at three sites along the lower Tana River (Kenya), based on monthly sampling between January 2009 and December 2011. Concentrations of total suspended matter (TSM), particulate organic carbon (POC), dissolved organic carbon (DOC), and dissolved inorganic carbon (DIC) were monitored, as was the stable isotope composition of the carbon pools. Both TSM and POC concentrations showed strong seasonality, varying over several orders of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 38 publications
1
33
1
Order By: Relevance
“…However, the amount of floodplain OC deposition is smaller than the total OC loss from the river system between Garissa and Tana Primate Reserve as estimated by Tamooh et al [2014], (53-68 Gg C yr À1 ), despite the fact that Tana Primate Reserve is located~80 km upstream of Garsen.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…However, the amount of floodplain OC deposition is smaller than the total OC loss from the river system between Garissa and Tana Primate Reserve as estimated by Tamooh et al [2014], (53-68 Gg C yr À1 ), despite the fact that Tana Primate Reserve is located~80 km upstream of Garsen.…”
mentioning
confidence: 81%
“…Here we present a study on C deposition and burial in the Tana River, a tropical river system located in Kenya. The lower Tana River has extensive floodplains and it has been suggested that substantial quantities of sediments and OC are retained within the system [Tamooh et al, 2014].…”
Section: Omengo Et Al Organic Carbon In a Tropical Floodplainmentioning
confidence: 99%
“…The historical paucity of datasets representing tropical river systems has been a strong impetus for the burgeoning research on sediment and C fluxes within these systems over the past decade, and has also witnessed a broadening geographical coverage: while the Amazon has traditionally functioned as the archetype for tropical rivers (Abril et al, 2014;Mayorga et al, 2005;Moreira-Turcq et al, 2003Richey et al, 2002), there has been an increase in data availability from other systems in Latin-America (Depetris and Kempe, 1993;Laraque et al, 2013;Mora et al, 2014), as well as a range of systems 15 in Asia (Aldrian et al, 2008;Bird et al, 2008;Sarin et al, 2002;Zhou et al, 2013), small islands (Lloret et al, 2011;Wiegner et al, 2009), and Africa (Borges et al, 2015;Bouillon et al, 2012;Brunet et al, 2009;Coynel et al, 2005;Tamooh et al, 2014;Wang et al, 2013;Zurbrügg et al, 2013).…”
mentioning
confidence: 99%
“…Monitoring 20 campaigns most often achieve only monthly measurements or, in a few cases, 2-weekly or weekly measurements (e.g. Bouillon et al, 2012;Brunet et al, 2009;Tamooh et al 2014). The monitoring period in most cases lasted one or two years.…”
mentioning
confidence: 99%
See 1 more Smart Citation